Local and remote management integration for flexible service provisioning to the home. - Nikolaidis, Apostolos E. (IEEE Communications magazine)
Giving the operator the ability to manage in- home devices greatly increases the potential of the cost-efficient provision of new profitable services. In this spirit, standardization undertaken by the DSL forum not only addresses remote management of the residential gateway but recently, also extends to in-house devices. We propose a solution that bridges remote management specified by CWMP with UPnP, already established inside the home environment. This approach will enable providers to remotely configure and manage in-house UPnP-enabled equipment, thus accelerating the deployment of new services. We investigate the nature of the two protocols and specify the bridging functionality, taking into consideration scalability and transparency. Experimental results support the applicability of the proposed approach, highlight the importance of message filtering, and provide general insight into the interplay intricacies of the particular protocol functions.